An upconversion nanoparticle enables near infrared-optogenetic manipulation of the Caenorhabditis elegans motor circuit - Ao, Yanxiao (2021)
Near-infrared (NIR) light penetrates tissue deeply, but its application to motor behavior stimulation has been limited by the lack of known genetic NIR light-responsive sensors. We designed and synthesized a Yb³⁺/Er³⁺/Ca²⁺-based lanthanide-doped upconversion nanoparticle (UCNP) that effectively converts 808 nm NIR light to green light emission. This UCNP is compatible with Chrimson, a cation channel activated by green light; as such, it can be used in the optogenetic manipulation of the motor behaviors of Caenorhabditis elegans. We show that this UCNP effectively activates Chrimson-expressing, inhibitory GABAergic motor neurons, leading to reduced action potential firing in the body wall muscle and resulting in locomotion inhibition. The UCNP also activates the excitatory glutamatergic DVC interneuron, leading to potentiated muscle action potential bursts and active reversal locomotion. Moreover, this UCNP exhibits negligible toxicity in neural development, growth, and reproduction, and the NIR energy required to elicit these behavioral and physiological responses does not activate the animal's temperature response. This study shows that UCNP provides a useful integrated optogenetic toolset, which may have wide applications in other experimental systems.